Overexpression of pyruvate dehydrogenase phosphatase 1 promotes the progression of pancreatic adenocarcinoma by regulating energy-related AMPK/mTOR signaling - Ye Li (Cell & Bioscience, 2020)
Abstract Background Human pyruvate dehydrogenase phosphatase 1 (PDP1) plays an important physiological role in energy metabolism; however, its expression and function in human pancreatic adenocarcinoma (PDAC) remain unknown. This study aimed to investigate the expression pattern and mechanisms of action of PDP1 in human PDAC. Methods The expression pattern of PDP1 in PDAC was determined, and its correlation with patient survival was analyzed. Ectopic expression or knockdown of PDP1 was performed, and in vitro proliferation and migration, as well as in vivo tumor growth of PDAC, were measured. The mechanism was studied by biochemical approaches. Results PDP1 was overexpressed in human PDAC samples, and high expression of PDP1 correlated with poor overall and disease-free survival of PDAC patients. PDP1 promoted the proliferation, colony formation, and invasion of PDAC cells in vitro and facilitated orthotopic tumor growth in vivo. PDP1 accelerated intracellular ATP production, leading to sufficient energy to support rapid cancer progression. mTOR activation was responsible for the PDP1-induced tumor cell proliferation and invasion in PDAC. AMPK was downregulated by PDP1 overexpression, resulting in mTOR activation and cancer progression. Conclusion Our findings suggested that PDP1 could be a promising diagnostic and therapeutic target for anti-PDAC treatment.